f( x ) = a * ( 1 - exp( b * x ) ) Regression for the decaying exponential function.
« More »f( x ) = a * ( 1 - exp( b * x ) ) + c Regression for the decaying exponential function with offset.
« More »f( x ) = a * ( 1 - exp( b * x + c ) ) + d Regression for the decaying exponential function with two offsets.
« More »f( x ) = a * exp( b * x ) Regression for the basic exponential function.
« More »f( x ) = a * exp( b * x ) + c Regression for the exponential function with an offset.
« More »f( x ) = a * x^b Regression for the basic exponentiation function.
« More »f( x ) = a * x^b + c Regression for the basic exponentiation function.
« More »f( x ) = a * n^( b * x ) Regression for the basic exponentiation function.
« More »f( x ) = a * n^( b * x ) + c Regression for the basic exponentiation function.
« More »f( x ) = a * b^( c * x ) Regression for the basic exponentiation function.
« More »f( x ) = a * b^( c * x + d ) Regression for the basic exponentiation function.
« More »